AB0943 Reliability of Musculoskeletal Ultrasound To Detect Elementary Lesions in Juvenile Idiopathic Arthritis. (15th July 2016) - Hernández Díaz, C.; Ventura-Ríos, L.; De la Cruz Becerra, L.; Barzola, L.; Rodríguez García, A.; Sanchez Bringas, G.; Faugier, E.; Roth, J.
Abstract : Background: Clinical evaluation has limitations to detect inflammation in JIA. Musculoskeletal ultrasonography (MSKUS) is a useful tool to detect inflammation in various arthropathies, but in children has not been validated for detection of elementary lesions such as synovitis [effusion (SE) and synovial hypertrophy (SH)], erosions, tenosynovitis (TNS) and cartilage damage. Objectives: To evaluate the reliability of MSKUS to detect carpal and metacarpal joint synovitis in patients with JIA. Methods: Seven patients with JIA diagnose according to ILAR criteria were included; they were evaluated by MSKUS for 5 ultrasonographers to evaluate synovitis, erosions, TNS and cartilage in the carpal joint, 2nd and 3rd metacarpophalangeal joints bilaterally; in 2 rounds in one day. Intra- and interobserver variability was established with Cohen's kappa, according to Landis and Koch classification. Results: The mean age of the children was 9 years old; disease duration of 5 years. The inter-observer DS, HS, TNS and erosions agreement was good to excellent (k=.88 0.5889–1.0 95%, p=0.0000) and moderate for cartilage (k=0.43, 95% CI 0.0545 to 0.8964, p=0). The intra-observer variability was good (0.71, IC95% from 0.591 to 0.8498, p=0.0000). Conclusions: The US is reliable for assessing the presence of synovitis, tenosynovitis, erosion and cartilage in hands, in patients with JIA. Disclosure of Interest: None declared